2020
DOI: 10.1124/mol.120.119412
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Caffeine Synergizes Adverse Peripheral and Central Responses to Anesthesia in Malignant Hyperthermia Susceptible Mice

Abstract: Ryanodine receptor (RYR) mutations confer stress-triggered malignant hyperthermia susceptibility (MHS). Dietary caffeine (CAF) is the most commonly consumed psychoactive compound by humans. CAF-triggered Ca 2+ release and its influences on skeletal muscle contractility are widely used as experimental tools to study RYR function/dysfunction and diagnose MHS. We hypothesize that dietary CAF achieving This article has not been copyedited and formatted. The final version may differ from this version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Because of the known effects of volatile anesthetics on RyR1 in skeletal muscle in MH, direct interaction with RyR1 is likely involved in the neuronal effects of volatile anesthetics on ER Ca 2+ . A recent pilot study in heterozygous R163C-RYR1 MH-susceptible mice showed enhanced suppression of CNS electrical activity by the volatile anesthetic halothane in vivo consistent with CNS effects of an MH-associated RYR1 mutation ( Aleman et al, 2020 ). Caffeine, an RyR agonist, enhanced halothane suppression of EEG power in R163C-RYR1 mice, suggesting that a volatile anesthetic has functional CNS phenotype in MH-susceptible mice.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Because of the known effects of volatile anesthetics on RyR1 in skeletal muscle in MH, direct interaction with RyR1 is likely involved in the neuronal effects of volatile anesthetics on ER Ca 2+ . A recent pilot study in heterozygous R163C-RYR1 MH-susceptible mice showed enhanced suppression of CNS electrical activity by the volatile anesthetic halothane in vivo consistent with CNS effects of an MH-associated RYR1 mutation ( Aleman et al, 2020 ). Caffeine, an RyR agonist, enhanced halothane suppression of EEG power in R163C-RYR1 mice, suggesting that a volatile anesthetic has functional CNS phenotype in MH-susceptible mice.…”
Section: Discussionmentioning
confidence: 82%
“…While the mechanisms underlying the skeletal muscle manifestations of MH are understood in reasonable detail, there are few reports of the effects of MH mutations on neuronal function. In the absence of hyperthermia and muscle rigidity, depression of CNS electrical activity has been reported in R163C-RYR1 MH-susceptible mice after exposure to the volatile anesthetic halothane ( Aleman et al, 2020 ). However, this has not been investigated at the cellular level, in other MH models including the RYR1 T4826I mutation, or with modern anesthetic ethers such as isoflurane.…”
Section: Introductionmentioning
confidence: 99%